2013
DOI: 10.1089/omi.2012.0064
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Hepatoprotective Effects for Scoparone Using MALDI-TOF/TOF Mass Spectrometry with Bioinformatics

Abstract: Scoparone is an active ingredient of Yinchenhao (Artemisia annua L.), a well-known Chinese medicinal plant, and has been utilized in prevention and therapy of liver damage. However, the molecular drug targets associated with the pharmacological effects of scoparone are largely unknown. In the present article, we extend the previous research on Yinchenhao through a study of its active ingredient and thus the putative targets of scoparone. We employed two-dimensional gel electrophoresis, and all proteins express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Modern pharmacological studies have shown it is a major constituent of Artemisia capillaris Thunb. that is quickly absorbed and slowly eliminated345. For thousands of years, Artemisia capillaris Thunb.…”
mentioning
confidence: 99%
“…Modern pharmacological studies have shown it is a major constituent of Artemisia capillaris Thunb. that is quickly absorbed and slowly eliminated345. For thousands of years, Artemisia capillaris Thunb.…”
mentioning
confidence: 99%
“…Modern pharmacology has demonstrated that YCHT has various kinds of pharmacological effects, including anti‐hepatic fibrosis, anti‐inflammatory, and hepatoprotective effects . Clinically, YCHT can be widely applied to alleviate chronic hepatitis B, liver cirrhosis, hepatic fibrosis, and cholestasis liver injury . The traditional YCHT decoction method (named separated decoction) is prepared in four steps as follows: (1) immersion of Artemisia capillaries Thunb, (2) boiling Artemisia capillaries Thunb, (3) adding and boiling Fructus Gardenia jasminoides Ellis and Rheum officinale Baill, and (4) boiling everything together once more.…”
Section: Introductionmentioning
confidence: 99%
“…Omics approaches combined with other biochemical methods can reconstruct regulatory networks, signaling cascades, and metabolic pathways upon drug treatment (Zhang et al, 2013b). The identification of their targets is required for a comprehensive understanding of their pharmacological role, and for unraveling their mechanism of action.…”
Section: Introductionmentioning
confidence: 99%